'Talking Very Properly Creates Such a Distance': Exploring Style-Shifting in Speech-Language Therapists - Rombouts, Ellen; Fieremans, Myrthe; Zenner, Eline (International journal of language & communication disorders, 2023)
Background: In the governmental delineation of the speech-language therapist (SLT) profession and in preservice SLT education, Flemish SLTs are considered as gatekeepers of the standard language in Flanders. Yet, most Flemish clients typically use a colloquial language style. Following earlier research on how teachers' language style affects teacher-student interactions, an SLT's strict adherence to standard Dutch may potentially evoke perceptions of inequality in their clients. As a result, Flemish SLTs may find themselves torn between on the one hand adhering to the standard language and on the other hand adapting to the sociolinguistic style of their client and establishing trust. In the present study, we explored SLTs' views on using standard/colloquial language varieties in their practice. Methods & Procedures: Individual semistructured interviews were conducted with 13 Flemish SLTs who worked with children, adolescents and adults in special schools, private practices and hospitals. Interview transcripts were analysed with reflexive thematic analysis. Outcomes & Results: Analyses yielded three themes. Switching between styles was (1) triggered by client characteristics (age, style, therapeutic needs), and it was shaped by (2) the need for establishing trust and (3) a balance between the SLT's professional and personal identity. Notably, most SLTs described partially converging with their clients' colloquial style, effectively reconciling their professional identity as expert speakers with their personal identity as a colloquial language user. Conclusions & Implications: Despite consensus on the role of the SLT as gatekeeper of standard language, many SLTs felt that colloquial language also plays an important role as it bolsters therapeutic alliance and rehabilitation of functional communication. By implementing reflective mixed methods and integrating the client perspective, future studies should further examine how authentic style-switching occurs and how various styles used by the SLT are evaluated by clients in different contexts. These findings may guide the development of style-switching as a communicative strategy that can be addressed in preservice education.